Randomized head-to-head comparison of minodronic acid and raloxifene for fracture incidence in postmenopausal Japanese women: the Japanese Osteoporosis Intervention Trial (JOINT)-04. (1st November 2020) - Uemura, Yukari; Sone, Teruki; Tanaka, Shiro; Miyazaki, Teruhiko; Tsukiyama, Mayumi; Taguchi, Akira; Soen, Satoshi; Mori, Satoshi; Hagino, Hiroshi; Sugimoto, Toshitsugu; Fukunaga, Masao; Ohta, Hiroaki; et al.
Abstract: Aims: We conducted a head-to-head randomized trial of minodronate, a bisphosphonate, and raloxifene, a selective estrogen receptor modulator, to obtain clinical evidence and information about their efficacy and safety. Methods: The Japanese Osteoporosis Intervention Trial protocol number 4 (JOINT-04) trial is a multi-center, open-labeled, blinded endpoints, head-to-head randomized trial of minodronate and raloxifene. Ambulatory elderly women with osteoporosis (age, >60 years) were randomly allocated to the raloxifene or minodronate group by central registration. The co-primary endpoints included any one of osteoporotic fractures (vertebral, humeral, femoral, and radial fractures), vertebral fractures, and major osteoporotic fractures (clinical vertebral, humeral, femoral, and radial fractures). The biological effects of each drug, patients' quality of life, and drug safety were assessed based on the secondary outcomes. This study was registered at the University Hospital Medical Information Network-Clinical Trials Registry (UMIN-CTR) under trial identification number UMIN000005433. Results: A total of 3896 patients were randomized to the minodronate and raloxifene groups, and drug efficacy assessments were performed for 3247 patients (1623 and 1624 patients, respectively). Among these patients, 1176 and 1187 patients received allocated treatment for 2 years. The incidence rate ratios for osteoporotic, vertebral, and major osteoporotic fractures in the minodronate group were 0.94 (95% CI: 0.78–1.13, p = .494), 0.86 (95% CI: 0.70–1.05, p = .147), and 1.22 (95% CI: 0.86–1.74, p = .274), respectively. Compared to the raloxifene group, the minodronate group showed significantly increased bone mineral density of the lumbar spine for each visit (6 months: p = .007, 12 months: p = .0003, 24 months: p <.0001). Also, serious adverse reactions were observed for four and six patients in the minodronate and raloxifene groups, respectively. Conclusions: Overall, there were no statistical differences in the incidence rates of osteoporotic, vertebral, or major osteoporotic fractures between the two groups. Serious adverse reactions were rare in both groups.